Towards a Business Model Framework to Increase Collaboration in the Freight Industry - Alix Vargas; Shushma Patel; Dilip Patel (Logistics)
Collaboration in the freight industry has not been widely adopted mainly due to the perceived barriers in competition resulting in a lack of trust among fleet operators. Collaboration in this sector has significant benefits, including the reduction of empty running, operating costs (OPEX) and greenhouse gas emissions (GHG) resulting in greater utilisation of existing logistics assets. A review of the literature to establish the critical aspects of freight collaboration was undertaken, as well as analyses of published case studies and European Union (EU)-funded projects. The critical aspects and barriers identified include: revenue sharing; compliance with competition law; process synchronization; organisational and systems interoperability; different forms of collaboration from a physical and coordination structure perspective; and strategies for collaboration. To facilitate collaboration a freight collaborative business model (FCBM) framework that highlights problematic areas in freight collaboration is proposed to support standardizing collaborative practices in the freight industry. Three published freight industry collaboration business cases were evaluated against the model. The business model framework is intended as a tool to be used to compare different business models and identify the best innovations to help facilitate collaborative practices. The freight collaboration business model was applied to the Freight Share Lab research project in order to demonstrate the concept and investigate whether efficiency can be unlocked through deployment of a dynamic data and asset sharing platform to enable route and load optimization across multiple fleets of freight vehicles, rail freight wagons and containers.